Bias caused by reliance on patient-reported outcome measures in non-blinded randomized trials: an in-depth look at exercise therapy for chronic fatigue syndrome. Issue 4 (1st October 2020) - Tack, Michiel; Tuller, David M.; Struthers, Caroline
ABSTRACT: Background: Several randomized trials have reported that graded exercise therapy (GET) is an effective treatment for chronic fatigue syndrome (CFS). These trials were not blinded and relied on patient-reported outcome measures (PROMs). We investigate whether bias introduced by this study design influenced the results. Methods: We extracted standardized mean differences from the most recent meta-analysis on exercise therapy for CFS to analyze their size, consistency over time, and congruence with objective measurements. A narrative review methodology was used to examine mediation analyses, plausible mechanisms of improvement, and risk of response bias. Results: Patient-reported improvements in exercise trials for CFS tend to be small, transient, and poorly supported by objective measurements. The risk of expectancy effects and response bias was high as patients were actively encouraged to adopt a positive attitude towards exercise therapy. Mediation analyses suggest that self-reported improvements in fatigue and physical function are not mediated by objective measures of fitness. Conclusions: Treatment effects seen in exercise trials for CFS could be the result of bias associated with the use of PROMs in non-blinded trials. This might explain the discrepancy between positive results reported in randomized trials and views on exercise therapy expressed by patient organizations. We hope that this case study furthers critical assessment of patient-reported improvements in areas of medicine where blinding of therapists and trial participants faces practical limitations.